ARISTOTLE ON RHETORIC AND POLITICAL PERSUASIVE SKILLS: EXAMPLES FROM POLITICAL CAMPAIGNS IN AFRICAN POLITICS - Longino Rutagwelera Kamuhabwa, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Aristotle’s theory and principles of Rhetoric have an application to political communication. In this paper, we make a descriptive, critical and analytical exposition of the features of Rhetoric according to Aristotle with a focus on their application to political campaigns in Africa and elsewhere. While exposing the persuasive skills of Rhetoric we associate them with some logical fallacies which political speakers commit in their maneuvers to win credibility before the electorates. As Rhetoric is essentially an art of persuasion it is prone to some immoral stances. These may include deceiving and objectifying the audience for the political interests of the speakers, reciprocation of defamatory and hate speeches among political speakers, inciting of hatred and violence, etc. all aiming at persuading the electorate at all cost and by all means.